2022
DOI: 10.3390/nano12020219
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Performance of BaMnO3 Perovskite as Soot Oxidation Catalyst Using Carbon Black during Sol-Gel Synthesis

Abstract: A series of BaMnO3 solids (BM-CX) were prepared by a modified sol-gel method in which a carbon black (VULCAN XC-72R), and different calcination temperatures (600 °C–850 °C) were used. The fresh and used catalysts were characterized by ICP-OES, XRD, XPS, FESEM, TEM, O2-TPD and H2- TPR-. The characterization results indicate that the use of low calcination temperatures in the presence of carbon black allows decreasing the sintering effects and achieving some improvements regarding BM reference catalyst: (i) smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(53 citation statements)
references
References 68 publications
7
46
0
Order By: Relevance
“….1 in the Appendix A), indicate that, as observed in the absence of copper [25], most of the carbon black has been efficiently removed during the synthesis as the percentage of remaining carbon black ranges from 6% for BMC3-C600 to 1% for BMC3-C850 (see data in Table A.1 in the Appendix A).…”
Section: Characterization Of Fresh Catalysts 149mentioning
confidence: 88%
See 4 more Smart Citations
“….1 in the Appendix A), indicate that, as observed in the absence of copper [25], most of the carbon black has been efficiently removed during the synthesis as the percentage of remaining carbon black ranges from 6% for BMC3-C600 to 1% for BMC3-C850 (see data in Table A.1 in the Appendix A).…”
Section: Characterization Of Fresh Catalysts 149mentioning
confidence: 88%
“…[26]. As observed for BM-CX catalysts series [25], the use of carbon black allows the synthesis of perovskite-like mixed oxides (BaMnO 3 hexagonal PDF number: 026-0168, denoted by the ICDD) at lower temperatures than the conventional sol-gel method [26]. Additionally, it is observed that the formation of the BaMnO 3 polytype, the main crystal phase in BMC3 [26], is hindered in presence of carbon black.…”
Section: Chemical Composition: Icp-oesmentioning
confidence: 91%
See 3 more Smart Citations